Māṇḍūkyopanishadbhāshyārtha, mūḷa, artha, Gaudapādīyakārikā tyācā artha va bhāshya ỹāsaha - Bāpaṭa, Vishṇu Vāmana, 1871-1932 (SAMP early 20th-century Indian books project ;, 1917)
Study of Māṇḍūkyopaniṣad and Gauḍapādakārikā, expounding Hindu Advaita philosophy.